Empirical Approach of Tax Avoidance Risk Assessment - Satyadini, Agung Endika (Jurnal Kajian Ekonomi dan Keuangan, 2018)
This study analyzes tax avoidance risk assessment including dimension and magnitude of tax avoidance risk exposure using several enterprise-related and government-related variables. Providing far-reaching analysis and examining a relatively unexplored area of conforming tax avoidance, this study employs two measurements of tax avoidance including non-conforming and conforming tax avoidance. As an extensive analysis, this paper also examines the magnitude of tax avoidance responsiveness with respect to different types of enterprises including Permanent Establishment and foreign-invested enterprises. The results drawn from this study are paramount as the empirical approach to in tax policy formulation. Risk profiles suggested in this research are pertinent to risk engine of Compliance Risk Management (CRM) and also beneficial for Risk-Based Audit strategy formulation. Ensuring the best-fit policy formulation, these results revealed that application of tax authority’s strategy to hike tax compliance should be more likely to prevention rather than reaction. Furthermore, in the brain area of academic research, the findings also contribute to the field of tax literature by providing simultaneous empirical models including conforming and non-conforming tax avoidance model, which has been relatively unexplored in prior studies.